Konstruksi Kebahagiaan dalam Pandangan al-GhazÄlÄ«: Antara MisykÄh, KÄ«myÄâ€™ dan Miâ€˜yÄr - Mahbub Ghozali; Chandra Kartika Dewi (Jurusan Tasawuf dan Psikoterapi Fakultas Ushuluddin, Adab dan Dakwah UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
The construction of happiness in al-GhazÄlÄ«â€™s view is unique than a concept of happiness in the other Sufismâ€™s though which are more directed to the happiness of the hereafter. Al-GhazÄlÄ« gives the view that the happiness of the hereafter can only be achieved if the happiness of this world has been fulfilled. This study aims to find the process and transformation of happiness achieved in the world to form happiness in the hereafter. To achieve this goal, this study uses a qualitative method with a content analysis tool. This study shows that the achievement of happiness starts from the most basic structure, namely the body as a foothold (misykÄh). The body with all its body parts doing what is beautiful actions and in accordance with sharia. This action will lead to happiness in the world. However, the actions of the body parts are controlled from within by the heart in synergy with the mind as the source of knowledge. The synergy of both of them maintain the stability of actions so that they do not deviate from the standards (miâ€™yÄr) that are determined until they are transformed into happiness in the hereafter with maâ€™rifah Allah (seeing the God).